Effects of planting pattern and cultivar on weed and crop growth in aerobic rice system - Mahajan, Gulshan; Chauhan, Bhagirath S. (Cambridge University Press, 2011)
Weeds are a major biotic constraint to aerobic rice production in Asia. Research is needed on the effects of cultural practices on weed management in aerobic rice, including techniques such as planting pattern and competitive cultivars. Field experiments were conducted in Punjab, India, in the wet seasons of 2008 and 2009 to study the growth of weeds and two rice cultivars [PR 115 and Punjab (P.) Mehak 1] in relation to planting pattern (uniform rows [23-cm row spacing] and paired rows [15-, 30-, and 15-cm row spacings]) under aerobic conditions. Junglerice and rice flatsedge were the dominant weed species during the early stages of the crop, while Chinese sprangletop and large crabgrass were the predominant species during flowering stage of the crop. Weed dry matter was not affected by planting pattern of P. Mehak 1; however, for PR 115, weed dry matter was greater in rice grown in uniform rows (244 g m−2) than in paired rows (183 g m−2). Planting patterns did not affect weed-free crop growth and yield, but weeds tended to be more abundant in the uniform planting system, particularly under cultivar PR 115. Consequently, this cultivar grew and yielded better under the paired rows when weeds were present. The cultivar PR 115 had greater yield potential than P. Mehak 1, but growth and productivity of P. Mehak 1 were unaffected by the planting patterns, suggesting better competitive ability against weeds than PR 115. The results imply that yield of some aerobic rice cultivars may be improved by exploring competitiveness of rice cultivars through paired row planting patterns. There is a need to study plasticity changes for cultivars which respond with more competiveness in paired rows. The identified traits could be useful as selection criteria for screening weed-competitive cultivars in paired row pattern.